l-Arginine supplementation or arginase inhibition augments reflex cutaneous vasodilatation in aged human skin - Holowatz, Lacy A (Blackwell Science Inc, 2006)
Full expression of reflex cutaneous vasodilatation is dependent on nitric oxide (NO) and vasodilatation is attenuated in healthy older humans. NO bioavailability in aged skin may be decreased by an age-related upregulation of arginase, which reciprocally regulates the NO-synthase (NOS) substrate l-arginine (l-Arg). We hypothesized that increased arginase activity contributes to attenuated vasodilatation in aged skin by limiting l-Arg for NOS-mediated NO synthesis. Five microdialysis fibres were placed in forearm skin of 10 young (Y, 23 ± 1 years) and 9 older (O, 68 ± 1 years) human subjects, serving as control (C, Ringer solution), NOS-inhibited (10.0 mmN(G)-nitro-l-arginine), arginase-inhibited (5.0 mm (S)-(2-boronoethyl)-l-cysteine + 5.0 mmN(ω)-hydroxy-nor-l-arginine), l-arg supplemented (l-Arg; 10.0 mml-arginine) and combined arginase-inhibited + l-Arg sites. After 20 min thermoneutral baseline, cutaneous vasodilatation was induced by passive whole-body heating to increase oral temperature (T(or)) by 1.0°C. Red blood cell flux was measured by laser-Doppler flowmetry over each microdialysis site. Cutaneous vascular conductance was calculated (CVC = flux/mean arterial pressure) and normalized to maximal CVC (CVC(max), 28.0 mm sodium nitroprusside + local heating to 43°C). Cutaneous vasodilatation during heating was attenuated in O (Y, 42 ± 1, versus O, 30 ± 1%CVC(max), P < 0.001) at control sites. NOS inhibition decreased vasodilatation in both age groups compared to C (Y, 22 ± 2; O, 18 ± 2%CVC(max); P < 0.001). Arginase inhibition, l-Arg supplementation, and arginase inhibition + l-Arg supplementation augmented vasodilatation in O (arginase-inhibited, 46 ± 4; l-Arg, 44 ± 4; arginase-inhibited + l-arg, 46 ± 5%CVC(max); P < 0.001 versus C) but not in Y (arginase-inhibited, 46 ± 4; l-Arg, 38 ± 4; arginase-inhibited + l-Arg, 44 ± 4%CVC(max); P > 0.05 versus C). Increasing l-Arg for NO synthesis by either arginase inhibition or direct l-Arg supplementation restores the age-related deficit in reflex cutaneous vasodilatation.